Penerapan Konsep Punakawan pada Interior Restoran Warung Apung Rahmawati di Surabaya - Pradjonggo, Celline Junica (Intra, 2014)
The charm of Surabaya culinary has grown well and has become as highly appealing as the other cities. Restaurants with traditional and modern concept are now in high demand, one of them is Warung Apung Rahmawati. This restaurant has grown big and successful. However Â Warung Apung Rahmawati isnt based on conceptualized branding. Therefore, the application of the concept of the interior of the WAR restaurant is very necessary to establish a brand image to the public. The concept taken is Punakawan. This concept was chosen to help reflect the main characteristic of Warung Apung Rahmawati restaurant. The character of Punakawan is applied visually into the elements of interior and decoration. The application of this new branding concept is not only meant to create a restaurant branding image towards the society, but also to create an interesting and comfortable atmosphere towards the consumers.